2017
DOI: 10.15296/ijwhr.2020.08
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire on Mothers’ Cultural Beliefs About Weaning: Development and Psychometric Evaluation

Abstract: Objectives: This study was designed to investigate the role of cultural beliefs on weaning. Therefore, the obtained results can be used for health policymakers who design strategies to prevent physical and mental damage to mothers and their children. The main objective of this study was to design a questionnaire probing the role of cultural beliefs on weaning. Materials and Methods: The sequential combination exploratory mixed methods design was used to develop the questionnaire format in two sections. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Besides the processes of initiating and maintaining breastfeeding, difficulties in the adaptation of mother and the infant after stopping breastfeeding may be experienced (10,14). Mothers may require information and support (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the processes of initiating and maintaining breastfeeding, difficulties in the adaptation of mother and the infant after stopping breastfeeding may be experienced (10,14). Mothers may require information and support (15).…”
Section: Discussionmentioning
confidence: 99%
“…Weaning practices can vary based on time and culture (12,13). Studies have indicated that mothers use numerous traditional methods during the weaning and the method they use has difficulties in adapting the mother and the infant to this process (10,14). Stopping breastfeeding an infant/child with ineffective methods such as creating bad taste or images before the mother and her infant /child are physically, emotionally and mentally ready, can lead to the feeling of punishment, feelings of insecurity, and a psychological trauma (7,9,11,13,15).…”
Section: Introductionmentioning
confidence: 99%